Epinephelus geoffroyi (Klunzinger, 1870) (Pisces: Serranidae), a valid species of grouper endemic to the Red Sea and Gulf of Aden - Randall, John E.; Bogorodsky, Sergey V.; Krupp, Friedhelm; Rose, Jean Michel; Fricke, Ronald (Zootaxa, 2013)
The grouper Epinephelus geoffroyi (Klunzinger), type locality Red Sea, previously regarded as a synonym of E. chlo-rostigma (Valenciennes) is recognized as a valid species. It is differentiated from E. chlorostigma by having 25–29 (mod-ally 27) gill rakers vs. 23–26 (modally 24), a more angular anal fin, the dark spots on the abdomen more widely separated, and lacking a clear white margin posteriorly on the caudal fin. The missing holotype of E. geoffroyi was found at the Staatliches Museum für Naturkunde Stuttgart (SMNS 233, 191 mm). Epinephelus chlorostigma is wide-ranging from the Gulf of Aden and east coast of Africa to Samoa; it is reported from the depth range of 32–280 m. Epinephelus geoffroyi is presently known only from the Red Sea and Gulf of Aden at depths of 3–32 m. Illustrations are provided for three other species of groupers with numerous small dark spots, E. areolatus (Forsskål), E. gabriellae Randall & Heemstra, and E. polylepis Randall & Heemstra, that are, or might be, sympatric with E. geoffroyi.